1996
DOI: 10.1177/001440299606300102
|View full text |Cite
|
Sign up to set email alerts
|

Middle and High School Students' Perceptions on Being Friends with Peers with Severe Disabilities

Abstract: A survey on friendships with peers with severe disabilities of 1,137 middle and high school students was conducted across three states. Students indicated that they should try to make friends with peers with severe disabilities and that friendships are most likely to develop when students with disabilities are educated in general education classes, for all or part of the school day. Students perceived themselves, special education teachers, and youth organizations as primarily responsible for facilitating thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 19 publications
0
20
0
10
Order By: Relevance
“…Another study demonstrated that inclusion facilitated a willingness to develop friendships between students with and without disabilities (Hendrickson, Shokoohi-Yekta, Hamre-Nietupski & Gable, 1996). Students without disabilities described learning from students with learning disabilities in the general classroom as a positive experience (Murray-Seegert, 1989).…”
Section: Types Of Service and Placement Optionsmentioning
confidence: 99%
“…Another study demonstrated that inclusion facilitated a willingness to develop friendships between students with and without disabilities (Hendrickson, Shokoohi-Yekta, Hamre-Nietupski & Gable, 1996). Students without disabilities described learning from students with learning disabilities in the general classroom as a positive experience (Murray-Seegert, 1989).…”
Section: Types Of Service and Placement Optionsmentioning
confidence: 99%
“…Por ejemplo, un facilitador sería una prótesis, que compensa una deficiencia por amputación en el miembro inferior, y que facilita la actividad de andar y correr, actividades clave en la participación en la mayoría de las actividades de EF. Maras y Brown, (1996);Collicort (2000); Hendrikson Shokoohi-Yekta, Hamre-Nietupski, y Gable (1996) 9. Otras estrategias:…”
Section: Condicionantes De La Práctica Inclusiva: Facilitadores Y Barunclassified
“…Esta creencia puede venir determinada tal y como expone la TCP, porque lo que no conocemos está sujeto a ideas preconcebidas, fruto de las experiencias y la información que recibimos de nuestro círculo social próximo, influyendo en la imagen en este caso sobre la discapacidad. Tras la participación en el programa, esta hipótesis parece confirmarse ya que, en este grupo se produce un cambio ya que pasan a identificarse a ellos mismos como el agente obstaculizador o facilitador de dicha inclusión, coincidiendo estos hallazgos con los obtenidos por Hendrickson et al (1996) en su estudio.…”
Section: Creencias Conductualesunclassified
See 2 more Smart Citations